Effects of Dietary Arginine and Glutamine on Alleviating the Impairment Induced by Deoxynivalenol Stress and Immune Relevant Cytokines in Growing Pigs - Wu, Li; Wang, Wence; Yao, Kang; Zhou, Ting; Yin, Jie; Li, Tiejun; Yang, Lin; He, Liuqin; Yang, Xiaojian; Zhang, Hongfu; Wang, Qi; Huang, Ruilin; et al. (PLOS ONE, 2013)
Deoxynivalenol (DON) is a mycotoxin that reduces feed intake and animal performance, especially in swine. Arginine and glutamine play important roles in swine nutrition. The objective of this study was to determine the effects of dietary supplementation with arginine and glutamine on both the impairment induced by DON stress and immune relevant cytokines in growing pigs. A total of forty 60-d-old healthy growing pigs with a mean body weight of 16.28±1.54 kg were randomly divided into 5 groups, and assigned to 3 amino acid treatments fed 1.0% arginine (Arg), 1.0% glutamine (Gln) and 0.5% Arg+0.5% Gln, respectively, plus a toxin control and a non-toxin control. Pigs in the 3 amino acid treatments were fed the corresponding amino acids, and those in non-toxin control and toxin control were fed commercial diet with 1.64% Alanine as isonitrogenous control for 7 days. The toxin control and amino acid treatments were then challenged by feeding DON-contaminated diet with a final DON concentration of 6 mg/kg of diet for 21 days. No significant differences were observed between toxin control and the amino acid groups with regard to the average daily gain (ADG), although the values for average daily feed intake (ADFI) in the amino acid groups were significantly higher than that in toxin control (P<0.01). The relative liver weight in toxin control was significantly greater than those in non-toxin control, arginine and Arg+Glu groups (P<0.01), but there were no significant differences in other organs. With regard to serum biochemistry, the values of BUN, ALP, ALT and AST in the amino acid groups were lower than those in toxin control. IGF1, GH and SOD in the amino acid groups were significantly higher than those in toxin control (P<0.01). The IL-2 and TNFα values in the amino acid groups were similar to those in non-toxin control, and significantly lower than those in toxin control (P<0.01). These results showed the effects of dietary supplementation with arginine and glutamine on alleviating the impairment induced by DON stress and immune relevant cytokines in growing pigs.